CMX-2043 Efficacy in a Rat Model of Cardiac Ischemia–Reperfusion Injury. (November 2016) - Baguisi, Alexander; Casale, Ralph A.; Kates, Steven A.; Lader, Alan S.; Stewart, Kenneth; Beeuwkes, Reinier
Α-Lipoic acid (LA) has been shown to offer protection against ischemia–reperfusion injury (IRI) in multiple organ systems. N -[(R)-1, 2-dithiolane-3-pentanoyl]-L-glutamyl-L-alanine (CMX-2043), a novel analogue of LA, was studied as part of a preclinical development program intended to identify safe and efficacious drug candidates for prevention or reduction in myocardial IRI. This study was designed to evaluate the efficacy of CMX-2043 in an animal model of myocardial IRI and to establish effective dosing conditions. CMX-2043 or placebo was administered at different doses, routes, and times in male Sprague-Dawley rats subjected to 30-minute left coronary artery ligation. Fluorescent microsphere injection defined the area at risk (AR). Animals were euthanized 24 hours after reperfusion, and the hearts were excised, sectioned, and stained with triphenyltetrazolium. Cytoprotective effectiveness was determined by comparing the unstained myocardial infarction zone (MI) to the ischemic AR. The reduction in the MI–AR ratio was used as the primary measure of drug efficacy relative to placebo injections. Treatment with CMX-2043 reduced myocardial IRI as measured by the MI–AR ratio and the incidence of arrhythmia. The compound was effective when administered by injection, both before and during the ischemic injury and at reperfusion. The most efficacious dose was that administered 15 minutes prior to the ischemic event and resulted in a 36% ( P < .001) reduction in MI–AR ratio compared to vehicle control.